A transdisciplinary approach to international teaching assistants : perspectives from applied linguistics - Looney, Stephen Daniel, 1982-; Bhalla, Shereen, 1980- (Multilingual Matters, 2019)
"The chapters in this volume offer state-of-the-art research into international teaching assistants in North American universities using a variety of methods and approaches, and as such constitute a transdisciplinary perspective which argues for the importance of dialogue between research and practice"--